Seasonally-Pumped-Storage on the São Francisco River:: increasing energy storage capacity and reducing evaporation losses - Hunt, Julian David; Freitas, Marcos Aurélio Vasconcelo; Pereira Junior, Amaro Olímpio (Sustainability in Debate, 2016)
The San Francisco river basin is very important for the country not only because of the volume of water that it transports through the Brazilian semi-arid region, but also on account of the potential for power generation and regional water supply. A challenge for the management of its water resources is the loss of water by evaporation in the Sobradinho reservoir. This article proposes the establishment of a new energy storage scheme that combines the operation of seasonal pumped-storage plants (SPS) with hydroelectric dams that operate in cascade, in order to increase the water and energy storage capacities and reduce evaporation in the Sobradinho reservoir. The proposed Muquém SPS has the potential to increase the national energy storage capacity by 4.8%, generate electricity during peak hours and store energy from wind and solar sources.